Fifteen-month-old infants use velocity information to predict others’ action targets - Stapel, Janny C.; Hunnius, Sabine; Bekkering, Harold (Frontiers in Psychology, 2015)
In a world full of objects, predicting which object a person is going to grasp is not easy for an onlooker. Among other cues, the characteristics of a reaching movement might be informative for predicting its target, as approach movements are slower when more accuracy is required. The current study examines whether observers can predict the target of an action based on the movement velocity while the action is still unfolding, and if so, whether these predictions are likely the result of motor simulation. We investigated the role of motor processes for velocity-based predictions by studying participants who based on their age differed in motor experience with the task at hand, namely reaching. To that end, 9-, 12-, and 15-month-old infants and a group of adults participated in an eye-tracking experiment which assessed action prediction accuracy. Participants observed a hand repeatedly moving towards and pressing a button on a panel, one of which was small, the other one large. The velocity of the reaching hand was the central cue for predicting which button would be the target of the observed action as the velocity was lower when reaching for the small compared to the large button. Adults and 15-month-old infants made more frequent visual anticipations to the close button when it was the target than when it was not and were thus able to use the information in the speed of the approach movement for the prediction of the action target. The 9- and 12-month-olds, however, did not display this difference. After the eye-tracking experiment, infants’ ability to aim for and press buttons of different sizes was evaluated. Results showed that the 15-month-olds were more proficient than the 9- and 12-month-olds in performing the reaching actions. The developmental time line of velocity-based action predictions thus corresponds to the development of performing that motor act yourself. Taken together, these data suggest that motor simulation may underlie velocity-based predictio